Intensitas Bimbingan Orang Tua Terhadap Perilaku Toilet Training Anak Usia 2-4 Tahun - Henny Panai; Lusiane Adam; Atika Parvati Kaharu (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2020)
Background: Toilet training is an exercise to control the discharge from the bladder so that the child is able to control the urination and defecation. The behavior of toilet training for each child is different depending on the characteristics of the child, the influence of the family environment, and the guidance from parents that is applied to the child.Objective: This study aims to analyze the relationship between the intensity of parental guidance and toilet training behavior for children aged 2-4 years.Methods: Using this type of cross-sectional research. The research subjects are all parents who have children aged 2-4 years. The sample in this study were 30 parents. The analytical method used is Chi Square.Results: The results of this study indicate that 6 (50%) respondents who did toilet training with insufficient guidance and 16 (88.9%) respondents who did not do toilet training but had good guidance. Based on the data analysis, a significant P value was obtained, namely 0.018 where P-value <0.05.Conclusion: There is a relationship between the intensity of parental guidance and toilet training behavior for children aged 2-4 years in Heledulaa Utara Village, Kota Timur District, Gorontalo City.